Exploring the potential of Bornean polypore fungi as biological control agents against pathogenic Ganoderma boninense causing basal stem rot in oil palm - Darlis, Darwana; Jalloh, Mohamadu Boyie; Chin, Clament Fui Seung; Mohamad Basri, Noor Khairani; Awang Besar, Normah; Ahmad, Khairulmazmi; Mohd. Rakib, Mohd. Rashid (Nature Research, 2023)
Basal stem rot due to a fungal pathogen, Ganoderma boninense, is one of the most devastating diseases in oil palm throughout the major palm oil producer countries. This study investigated the potential of polypore fungi as biological control agents against pathogenic G. boninense in oil palm. In vitro antagonistic screening of selected non-pathogenic polypore fungi was performed. Based on in planta fungi inoculation on oil palm seedlings, eight of the 21 fungi isolates tested (GL01, GL01, RDC06, RDC24, SRP11, SRP12, SRP17, and SRP18) were non-pathogenic. In vitro antagonistic assays against G. boninense revealed that the percentage inhibition of radial growth (PIRG) in dual culture assay for SRP11 (69.7%), SRP17 (67.3%), and SRP18 (72.7%) was relatively high. Percentage inhibition of diameter growth (PIDG) in volatile organic compounds (VOCs) in dual plate assay of SRP11, SRP17, and SRP18 isolates were 43.2%, 51.6%, and 52.1%, respectively. Molecular identification using the internal transcribed spacer gene sequences of SRP11, SRP17, and SRP18 isolates revealed that they were Fomes sp., Trametes elegans, and Trametes lactinea, respectively.